2016
DOI: 10.1098/rsbl.2016.0362
|View full text |Cite
|
Sign up to set email alerts
|

Does allopreening control avian ectoparasites?

Abstract: For birds, the first line of defence against ectoparasites is preening. The effectiveness of self-preening for ectoparasite control is well known. By contrast, the ectoparasite control function of allopreening-in which one birds preens another-has not been rigorously tested. We infested captive pigeons with identical numbers of parasitic lice, and then compared rates of allopreening to the abundance of lice on the birds over time. We documented a negative relationship between rates of allopreening and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
14
0
3
Order By: Relevance
“…In primates, the higher richness of socially transmitted parasites in species where social learning is more often recorded is in line with this idea (McCabe et al, 2014). Other cognitive traits may also be indirectly associated with socially transmitted parasitism, because of co-variation between these traits and social cognition (e.g., see Reader et al, 2011; see also Villa et al, 2016). Note however that sociality may also, in some cases, decrease parasite pressure, for example, via social defenses such as allogrooming/allopreening, or because of dilution effects (see Mooring and Hart, 1992), in which case social species should be less parasitized (e.g., Bordes et al, 2007).…”
Section: Mechanism 311: Social Intelligence and Social Parasitesmentioning
confidence: 64%
“…In primates, the higher richness of socially transmitted parasites in species where social learning is more often recorded is in line with this idea (McCabe et al, 2014). Other cognitive traits may also be indirectly associated with socially transmitted parasitism, because of co-variation between these traits and social cognition (e.g., see Reader et al, 2011; see also Villa et al, 2016). Note however that sociality may also, in some cases, decrease parasite pressure, for example, via social defenses such as allogrooming/allopreening, or because of dilution effects (see Mooring and Hart, 1992), in which case social species should be less parasitized (e.g., Bordes et al, 2007).…”
Section: Mechanism 311: Social Intelligence and Social Parasitesmentioning
confidence: 64%
“…An association between social breeding and allopreening has also been suggested, based on the hygienic benefits that allopreening provides ( Brooke 1985 ; Villa et al 2016 ). Focusing on cooperatively breeding species, Spottiswoode (2008) suggested that allopreening may have evolved in response to the increased risk of parasite transmission that results from close contact among group members (an argument that also holds for non-cooperative species breeding in dense colonies).…”
Section: Discussionmentioning
confidence: 99%
“…Allopreening can aid ectoparasite removal ( Brooke 1985 ; Villa et al 2016 ). However, if hygiene is the primary function of allopreening, why does this behavior occur in certain species only?…”
Section: Introductionmentioning
confidence: 99%
“…Birds were trapped consecutively in June 2014 and June 2015. Once trapped, pigeons were brought back to the laboratory, where their lice were killed by ethyl acetate fumigation in a chamber for 15 min, followed by gentle ruffling to dislodge the lice (Villa, Goodman, Ruff, & Clayton, ). Lice were counted and preserved in 95% ethanol for subsequent DNA extraction.…”
Section: Methodsmentioning
confidence: 99%